Strength training for soccer - Guzman, Daniel 1990-; Young, Megan 1984-; National Strength & Conditioning Association (U.S.).
"This book is an authoritative, practical guide to designing resistance training programs for soccer. It provides principles of resistance training, exercise descriptions, program design guidelines, and sample programs"
"Tailoring strength and conditioning programs for soccer requires a deep understanding of the demands of the game. Preparing players to accelerate, decelerate, change direction, and turn and jump can be a challenge. Developed with the expertise of the National Strength and Conditioning Association (NSCA), Strength Training for Soccer explains the value of resistance training for soccer players. The book-backed by practical experience, evidence-based training methodologies, and research-provides a general overarching biomechanical analysis of soccer and specific analysis of the physical demands of each position: goalkeepers, defenders, midfielders, and forwards. Using these analyses, you can design an effective training program that translates to performance on the field. The book also offers the following: 10 detailed protocols to test soccer players' strength, power, speed, agility, and high-intensity endurance capacity6 total body resistance exercises with 4 variations12 lower body exercises with 24 variations18 upper body exercises with 45 variations22 anatomical core exercises with 32 variations32 sample programs for off-season, preseason, in-season, and postseason resistance training Each resistance training exercise consists of a series of photos and a detailed list of primary muscles trained, beginning position and movement phases, breathing guidelines, modifications and variations, and coaching tips. You'll also learn proper exercise technique and gain a deeper understanding of what muscles are involved in each exercise so you can develop a complete and targeted resistance training program. Backed by the NSCA and the knowledge and experience of individuals who have years of experience as strength and conditioning professionals for soccer, Strength Training for Soccer is the authoritative resource for creating soccer-specific resistance training programs to help your athletes optimize their strength and successfully transfer that strength and power to the soccer field"
Foreword by Tim Howard -- Introduction by Bob Bradley -- Part I: principles of sport-specific resistance training -- Chapter 1: importance of resistance training / Garga Caserta and William E. Amonette -- Chapter 2: analysis of the sport and sport positions / Scott Piri -- Chapter 3: testing protocols and athlete assessment / Ernie Rimer and Jo Clubb -- Chapter 4: sport-specific program design guidelines / Megan Young, Garga Caserta, and Matt Howley -- Part II: exercise technique -- Chapter 5: total body exercise technique / Scott Caulfield and Bryan Mann -- Chapter 6: lower body exercise technique / Scott Caulfield and Bryan Mann -- Chapter 7: upper body exercise technique / Ian Jeffreys -- Chapter 8: anatomical core exercise technique / Cat Wade and Kevin Cronin -- Part III: program design guidelines and sample programs -- Chapter 9: off-season programming / Julia Eyre and Ivi Casagrande -- Chapter 10: preseason programming / Daniel Guzman and Joey Harty -- Chapter 11: in-season programming / Melissa Terry and Matt Howley -- Chapter 12: postseason programming / Ryan Alexander.
"National Strength and Conditioning Association."
MS Salazar (Recommending faculty) AY2022-2023
Includes bibliographical references and index.
Keywords: Soccer -- Training; Weight training; Muscle strength; SPORTS & RECREATION / Soccer; SPORTS & RECREATION / Coaching / Soccer